Bukan Sekadar Tempat Ngopi: Pemaknaan Subjektif Mahasiswa terhadap Coffee Shop di Kawasan Dago sebagai Informal Learning Space - Rizky Farhan Agusfian; Siti Komariah; Mirna Nur Alia Abdullah (Universitas Hamzanwadi, 2026)
The rapid growth of coffee shops in Indonesia, particularly in the Dago area of Bandung, has transformed these spaces from mere consumption sites into informal learning spaces for university students. Although research on coffee shops and students continues to develop, studies examining how students subjectively construct meaning around coffee shops as alternative learning spaces through the lens of Interaksionisme simbolik remain limited, especially in the specific context of Dago. This study aims to analyze in depth how students construct meaning around coffee shops in the Dago area as alternative learning spaces outside campus, using Blumer's Interaksionisme simbolik perspective. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with seven active students from Universitas Pendidikan Indonesia and one barista, as well as non-participant observation at three coffee shops in the Dago area, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings show that students' meaning-making of coffee shops as informal learning spaces occurs through three interrelated processes: the formation of a definition of the situation through physical symbols such as laptops and earphones, the construction of meaning through layered social interaction with fellow students, social media, and baristas, and the negotiation and modification of meaning through space appropriation practices and shifting collective discourse over time. These findings confirm that coffee shops in the Dago area are not merely a neutral backdrop, but an actively constructed social arena that extends students' learning space beyond the boundaries of formal institutions.